Trends in Mortality from Chronic Obstructive Pulmonary Disease in Alberta: Back to the Future? - Tee L Guidotti (Canadian Respiratory Journal)
Trends in mortality from chronic obstructive pulmonary disease (COPD) in Alberta over 60 years, from 1927 to 1987, for ages 15 and above or both sexes, were examined. There was a striking decline in mortality among older adults in the 1930s and 1940s. a nadir that lasted almost 10 years in the 1950s, and a striking increase thereafter. By 1970, most age groups had returned to levels of the 1930s. This overall trend was observed in both the younger age groups (aged 15 to 50) and older adults, although mortality from COPD in the former disproportionately reflected asthma-related deaths. Subsequently, mortality climbed still higher in older age groups, but not in the younger age groups. The sustained rise in mortality in older age groups after the Second World War is presumably related to smoking habits. Historical trends in Alberta were then compared with Canada as a whole for both sexes over 50 years of age. Although Alberta had a much lower mortality from COPD than Canada as a whole, this difference disappeared by 1980. There is no obvious explanation that would explain all of the observed trends, but they appear more likely to be a consequence of social and environmental conditions, including changes in health-related behaviour, than of major changes in medical management at the time.